Multispecies Biofilm Development of Marine Bacteria Implies Complex Relationships Through Competition and Synergy and Modification of Matrix Components - Guillonneau, Richard; Baraquet, Claudine; Bazire, Alexis; Molmeret, Maëlle (Frontiers in Microbiology, 2018)
Microbial communities composition is largely shaped by interspecies competition or cooperation in most environments. Ecosystems are made of various dynamic microhabitats where microbial communities interact with each other establishing metabolically interdependent relationships. Very limited information is available on multispecies biofilms and their microhabitats related to natural environments. The objective of this study is to understand how marine bacteria isolated from biofilms in the Mediterranean Sea interact and compete with each other when cultivated in multispecies biofilms. Four strains (Persicivirga mediterranea TC4, Polaribater sp. TC5, Shewanella sp. TC10 and TC11) with different phenotypical traits and abilities to form a biofilm have been selected from a previous study. Here, the results show that these strains displayed a different capacity to form a biofilm in static versus dynamic conditions where one strain, TC11, was highly susceptible to the flux. These bacteria appeared to be specialized in the secretion of one or two exopolymers. Only TC5 seemed to secrete inhibitory molecule(s) in its supernatant, with a significant effect on TC10. Most of the strains negatively impacted each other, except TC4 and TC10, which presented a synergetic effect in the two and three species biofilms. Interestingly, these two strains produced a newly secreted compound when grown in dual-species versus mono-species biofilms. TC5, which induced a strong inhibition on two of its partners in dual-species biofilms, outfitted the other bacteria in a four-species biofilm. Therefore, understanding how bacteria respond to interspecific interactions should help comprehending the dynamics of bacterial populations in their ecological niches.